Analisis Persepsi Masyarakat Terhadap Partisipasi Pengelolaan Sampah di Kelurahan Loa Bakung Kota Samarinda - Reni Wulandari; Moh. Mustakim; Jawatir Pardosi; Henny Pagoray; Eva Rachmi; Sri Wahyuningsih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify and analyze the relationship between the level of perception and the level of community participation in household waste management in Loa Bakung Village. The research employed both quantitative and qualitative methods using questionnaires, literature review, and direct observation. Respondents were selected using purposive sampling with a total of 80 participants. The results show a p-value of 0.001 ≤ α = 0.05 with a correlation coefficient of 0.361, indicating that there is a correlation between perception and participation in waste management, although the relationship is weak and positive. Qualitative findings reveal that waste banks can help reduce waste volume (66.3%) and highlight the importance of separating organic and inorganic waste (61.3%). However, actual participation remains limited, with only a small proportion of respondents regularly practicing waste sorting, composting, or recycling. The suggested recommendation is the need for awareness programs through KIE (Communicative, Implementation, and Education) approaches and regular monitoring.